INVESTIGATING THE EFFECTS OF PH ON THE SOLUBILITY OF EXPLOSIVE MATERIALS - Nmeka, Moses Azubuike; Ejenavi, Aderonke Peace (FUDMA JOURNAL OF SCIENCES, 2026)
The solubility behaviour of explosive materials plays a pivotal role in determining their environmental mobility, persistence, and safe handling. This study investigates the influence of pH on the solubility of representative explosive compounds, including nitroaromatics, nitramines, nitrate esters, and inorganic oxidizers. Experimental observations indicate that pH significantly affects solubility through ionization, hydrolysis and molecular stability mechanisms. Nitroaromatic compounds exhibit increased solubility under alkaline conditions, while nitrate esters undergo pH-dependent hydrolysis. Nitramines show limited sensitivity to pH variations, whereas inorganic oxidizers remain highly soluble across all conditions. These findings have important implications for environmental risk assessment, remediation strategies, and storage protocols.
Keywords: Explosives; Solubility; pH; Environmental fate; Hydrolysis; Nitroaromatics